Strengthening Positive Discipline through the Implementation of the TABANA Program to Address Bullying in Kindergarten and Primary Schools - Dhany Efita Sari; Sabar Narimo; Noor Lela Ahmad; Surya Jatmika; Suranto; Fiska Puspa Arinda; Nur Aeni Sa’adah; Raden Ahmed Abdillah (Universitas Muhammadiyah Surakarta, 2026)
The TABANA program was developed in response to the increasing prevalence of negative behaviors and bullying incidents in partner preschool and primary schools, which previously lacked a structured behavior management system. The program aims to foster a culture of positive behavior through a positive discipline approach supported by visual reinforcement strategies, including kindness jars, appreciation tokens, behavioral indicators, and data-based behavioral recapitulation. Program activities were conducted through socialization sessions, focus group discussions, teacher training, classroom implementation, mentoring, evaluation, and sustainability planning. Data were collected through non-verbal observations, teacher interviews, activity documentation, and weekly and monthly behavioral records, and subsequently analyzed using a descriptive–comparative approach to examine changes before and after program implementation. The findings indicate that more than 70% of students demonstrated improvements in positive behavior, particularly in terms of discipline, honesty, cooperation, and task completion at the primary school level. At the kindergarten level, consistent improvements were observed in queuing behavior, tidying up learning materials, and smiling, although behaviors related to sharing and self-regulation still require further reinforcement. The program also contributed to a reduction in negative behaviors, including mild forms of peer-to-peer bullying, and enhanced teachers’ capacity to manage classrooms and systematically evaluate student behavior. Overall, the TABANA program supports the creation of a more positive learning environment and establishes a sustainable foundation for character development in partner schools.